PEMANFAATAN VIDEO PEMBELAJARAN MENGGUNAKAN CANVA PADA KELAS IV SD NEGERI NO 174557 NAPITUPULU - Suciawati, Hasni; Manurung, Rolando Fernandes; Maria, Eka (Jurnal Curere, 2024)
Learning videos are learning media that utilize videos as a means of delivering learning material. Learning videos can be made using various applications, one of which is Canva. Canva is a graphic design application that is easy to use and has various features that can help create interesting and interactive learning videos, so teachers can use learning media through Canva to create interesting animations, infographics and explainer videos for fourth grade elementary school students. In conventional learning activities, teachers usually deliver material using the lecture method and then students are given assignments in the form of answering questions to see the students' abilities. However, this cannot be used again after learning activities at home which require teachers to create various methods to deliver the material. Apart from that, teaching staff are able to choose effective learning media in the learning process.  Learning media will help students master and understand the material presented by the teacher even though distance learning. Learning media can be adjusted based on the characteristics and abilities of students. Technological advances can be used as a basis for teachers to maximize learning activities. Effectiveness is the main factor in learning to ensure the successful use of learning models. Effectiveness can be explained as the act of student success. This process involves efforts and strategies that are implemented well and precisely. Therefore, the author in this study wants to see how effective the use of learning videos based on the Canva application is in the learning process. Teachers use this application as a learning medium for social studies subjects. This research aims to analyze the use of learning videos using Canva on the learning outcomes of fourth grade students at State Elementary Schools. No. 174557 Napitupulu.